2012
DOI: 10.4049/jimmunol.1102997
|View full text |Cite
|
Sign up to set email alerts
|

Innate NK Cells and Macrophages Recognize and Reject Allogeneic Nonself In Vivo via Different Mechanisms

Abstract: Both innate and adaptive immune cells are involved in the allograft response. But how the innate immune cells respond to allotransplants remains poorly defined. In the present study, we examined the role of NK cells and macrophages in recognizing and rejecting allogeneic cells in vivo. We found that in naïve mice NK cells are the primary effector cells in killing of allogeneic cells via “the missing self” recognition. However, in alloantigen pre-sensitized mice, NK cells are dispensable. Instead, macrophages b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 32 publications
1
74
0
3
Order By: Relevance
“…Consequently, the memory pool differs among individuals due to differences in immune history, pathogen exposures, and age. Memory cells are traditionally believed to be key features of adaptive immune cells (i.e., T cells and B cells), but recent studies have challenged this belief and further suggested that certain innate immune cells, such as NK cells and macrophages, can also acquire certain memory properties(1,2), a finding that is of great significance in transplantation.…”
Section: What Are Memory Cells and What Do They Do?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the memory pool differs among individuals due to differences in immune history, pathogen exposures, and age. Memory cells are traditionally believed to be key features of adaptive immune cells (i.e., T cells and B cells), but recent studies have challenged this belief and further suggested that certain innate immune cells, such as NK cells and macrophages, can also acquire certain memory properties(1,2), a finding that is of great significance in transplantation.…”
Section: What Are Memory Cells and What Do They Do?mentioning
confidence: 99%
“…However, recent studies suggest that certain types of innate immune cells, such as NK cells and macrophages, can also acquire memory features in that they can mediate robust recall responses. (1,2) Furthermore, in certain transplant models, subsets of memory cells have been recently shown to function as regulatory cells, and contrary to the initial belief, such memory T cells actually promote transplant survival. (3,4) Additionally, not all memory cells are committed to memory functions at all times.…”
Section: Introductionmentioning
confidence: 99%
“…This form of allorecognition may initiate or amplify the responses of recipient T cells to MHC and mHAg alloantigens by inducing the maturation of APCs. It could also provide phagocytic cells with the means to kill allogeneic targets without inflicting damage on self-tissues (Liu et al 2012). The ubiquity of allorecognition phenomena among sessile, colonial marine animals tempts one to speculate that mammalian innate allorecognition originated in invertebrate ancestors that routinely engaged in conspecific interactions in their natural habitats (Dishaw and Litman 2009).…”
Section: Are Innate Cells Alloreactive?mentioning
confidence: 99%
“…To date, it is known that IL-21 is primarily produced by natural killer T (NKT) cells and CD4 + T cells and has various activities on multilineages such as B-and T-cells, NKT cells, natural killer (NK) cells, and bone marrow-derived dendritic cells (BMDCs) [9]. Since both innate and adaptive immune cells contribute to allograft responses including T-and B-cells, NK cells, and macrophages in organ transplantation [10], it is conceivable that IL-21 and its receptor (IL-21R) are closely associated with transplant tolerance induction. Herein, our present article is the first to describe role of IL-21 signaling pathway in transplantrelated biology for better understanding.…”
Section: Introductionmentioning
confidence: 99%